Deciphering the motives, barriers and integration of Syrian refugee entrepreneurs into Turkish society: a SEM approach. Issue 1 (8th January 2021) - Almohammad, Dawoud; Durrah, Omar; Ahmed, Faisal
Abstract : Purpose: This study/paper aims to explore the effect of motives and barriers of Syrian refugee entrepreneurs on social and economic integration into Turkish society. Design/methodology/approach: Using a convenience sampling technique, data was collected using a questionnaire from 300 Syrian entrepreneurs who have entrepreneurial ventures in Turkey. The collected data was analyzed using structural equation modeling through an AMOS software. Findings: The results of this study indicate a significant influence of both individual and contextual motives on integration into Turkish society. However, the individual and contextual barriers do not appear to affect integration. Originality/value: This research contributes to the literature investigating the motives and barriers in relation to social and economic integration into Turkish society.